Tools to Communicate Urgency to Diminish Social Impacts on Water and Land - Rodriguez, Mario Buenfil; Visoso, Rosalinda Uribe (IJRDO-Journal of Applied Science, 2016)
Impacts on water land and natural resources from distinctive consumption and production patterns were assessed by using several waterand ecological footprint techniques. Typical consequences and comparison graphs of social groups from several countries were obtained. Thesefigures provide a comparison basis to orientate public policies and priorities for environmental and water education strategies and programs."New water culture" is a recent term which denotes a much needed cultural shift towards more respectful andconcrete actions which seek real sustainability, contrary the usual merely rhetorical sustainability. One of itsmain points is to hold back long "haulings" of real and virtual water; that is, reduce or eliminate unnecessarywater transfers among river basins and long and environmental inconvenient commercial shipping of its derivedcommercial and industrial produces. Nowadays the general global situation is of overshoot, unsustainability andanthropogenic climate alterations, so an important assessment is to compare if accumulative voluntaryreductions (probable) on individual consumptions and production patterns, could be stronger and higher thanthe demographic and ideological pushes on the contrary sense. That will give a better idea of the feasibility ofhaving any important success, or which other measures besides appealing to voluntary measures, ought to beimplemented.